A compact multiplanet system of three transiting giant planets around TIC 118798035 - Brahm, Rafael; Trifonov, Trifon; Jordán, Andrés; Henning, Thomas; Espinoza, Néstor; Rojas, Felipe I.; Tala Pinto, Marcelo; Jones, Matías I.; Thorngren, Daniel; Acuña, Lorena; Eberhardt, Jan; Reinarz, Yared; et al. (The astrophysical journal. Part 2, Letters, 2025)
We report the discovery and characterization of three transiting giant planets in the TIC 118798035 system. The three planets were identified as transiting candidates from data of the TESS mission and confirmed with ground-based photometric transit observations along with radial velocity variations obtained with FEROS, HARPS, and ESPRESSO. The three planets present transit timing variations (TTVs). We performed an N-body orbital fitting to the TTVs and radial velocities, finding that TIC 118798035 b is a warm low-density Neptune with a mass of 0.0250 ± 0.0023 MJ, a radius of 0.655 ± 0.018 RJ, and an orbital period of 11.507 days; TIC 118798035 c is a warm Saturn with a mass of 0.403 ± 0.024 MJ, a radius of 0.973 ± 0.023 RJ, and an orbital period of 22.564 days; and TIC 118798035 d is a warm Jupiter with a mass of 0.773 ± 0.052 MJ, a radius of 0.923 ± 0.044 RJ, and an orbital period of 48.925 days. The bulk metallicities of the three planets do not fully follow the mass-metallicity correlation found for the giant planets of the solar system, which hints at a somewhat different formation history for the planets of the TIC 118798035 system.
Online veröffentlicht: 11. Dezember 2025
Gesehen am 20.02.2026